1986
DOI: 10.1093/ajcn/44.4.501
|View full text |Cite
|
Sign up to set email alerts
|

Retention of zinc and calcium from the human colon

Abstract: Colonic retention of zinc and calcium was studied after installation during colonoscopy of 30 mumol of zinc and 6.4 mmol of calcium labeled with 65Zn and 47Ca, and measurement of the whole-body retention of the radionuclides. After cecal installation in nine patients, retention (day 13) of zinc was 3.5 +/- 2.1% (mean +/- SD) and of calcium 3.5 +/- 2.7%. The calculated mean absorption was 4.1% for zinc and 14.1% for calcium. Application at the hepatic flexure in four patients resulted in a mean retention (day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Subsequently, the absorption of free, short chain fatty acids will be met with a much more rapid response mediated by the exchanger. Since zinc is not hydrolyzed and only 10% of dietary zinc is absorbed (19), this ion is present at high concentrations along the entire digestive tract (19,20,39) and is thus ideally suited for a signaling role there.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, the absorption of free, short chain fatty acids will be met with a much more rapid response mediated by the exchanger. Since zinc is not hydrolyzed and only 10% of dietary zinc is absorbed (19), this ion is present at high concentrations along the entire digestive tract (19,20,39) and is thus ideally suited for a signaling role there.…”
Section: Discussionmentioning
confidence: 99%
“…This was reduced by ϳ30% at higher zinc concentrations (200 M). The results of this analysis show that zinc at concentrations found in the digestive tract (19,20,39), which induce Ca 2ϩ release through the ZnR (13), also trigger phosphorylation of ERK1/2.…”
Section: Specificity and Temporal Dependence Of Erk1/2mentioning
confidence: 95%
See 2 more Smart Citations
“…Reports on the relative contribution of the different sections of the intestine vary, and it has been suggested that the major site of absorption might shift with differences in food matrix and body Zn status. Absorption can occur throughout the total length of the small intestine, but colonic absorption is limited (Sandstrom et al 1986). Fractional Zn absorption falls with increasing dose (Istfan et al 1983), but increases fairly rapidly in response to reductions in dietary Zn intake (Wada et al 1985).…”
Section: S U S a N J Fairweather-taitmentioning
confidence: 99%